Molecular dynamics simulations of ejecta formation in helium-implanted copper. (15th March 2020) - Flanagan, R.M.; Hahn, E.N.; Germann, T.C.; Meyers, M.A.; Fensin, S.J.
Abstract: The effect of He concentration and morphology on ejecta production is investigated via molecular dynamics simulations. Identical He concentrations are inserted into Cu single crystals as interstitial atoms or bubbles near a flat free surface. The resulting ejecta is quantified through total mass, cluster size, and velocity of ejected particles. The presence of He increases total ejected mass as compared to pure Cu; He bubbles produce 56% more mass than atomic He. This increase is attributed to non-planarities in the shock front and reflected pulse due to He bubbles, akin to ejecta resulting from traditional Richtmeyer–Meshkov instabilities. Graphical abstract: Image, graphical abstract